Pediatric Neuroimaging Cases and Illustrations - Liu, Hongsheng; Zhang, Xiaoan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book aims to provide readers practical information on clinical diagnosis of pediatric neurological diseases. Topic areas include congenital malformations of the brain and cerebral vessels, brain tumors, intracranial infections, vascular diseases, metabolic encephalopathy, brain damage and destructive diseases. Utilizing a case-based format, the procedure of streamline disease recognition is presented in a clear and concise manner. Each case is supported by representative images, a discussion of the disease, and a description of the most characteristic imaging features of the disorder. Written by radiologists who have been involved pediatric imaging diagnosis for a long time, this case-based book will be a valuable reference for radiologists, paediatricians and neurologists, as well as those who are interested in related field.
1 Congenital Malformations of the Brain. 2 Brain Tumors -- 3 Intracranial Infection -- 4 Vascular Diseases -- 5 Metabolic Encephalopathy -- 6 Neonatal Craniocerebral Trauma -- 7 Brain Damage, Destructive Diseases -- 8 Neurodegenerative Diseases -- 9 Other Brain Diseases.
Keywords: Nervous system$1 (BRadiography.s; Neuroradiology; Brain Diseases; Brain Injuries; Brain -- diagnostic imaging; Child; Infant; Magnetic Resonance Imaging; Radionuclide Imaging; Case Reports